Developing and Implementing a Simulated Electronic Medication Administration Record for Undergraduate Nursing Education: Using Sociotechnical Systems Theory to Inform Practice and Curricula. Issue 3 (March 2017) - Booth, Richard G.; Sinclair, Barbara; Brennan, Laura; Strudwick, Gillian
Abstract : Knowledge and skills related to medication administration are a fundamental element of nursing education. With the increased use of electronic medication administration technology in practice settings where nurses work, nursing educators need to consider how best to implement these forms of technology into clinical simulation. This article describes the development of a simulated electronic medication administration system, including the use of sociotechnical systems theory to inform elements of the design, implementation, and testing of the system. Given the differences in the medication administration process and workflow generated by electronic medication administration technology, nursing educators should explore sociotechnical theory as a potentially informative lens from which to plan and build curricula related to simulation activities involving clinical technology.